A rare case of retinal migraine - Samanta, Shrishti; Kumar, Sanjay; Sinha, Keshav K.; Sinha, Rani I. (International Journal of Basic & Clinical Pharmacology, 2024)
Retinal migraine (ophthalmic migraine, ocular migraine, anterior visual pathway migraine) is a rarely encountered medical condition, but with an interesting and complex clinical presentation. Retinal migraine is defined as repeated attacks of monocular visual disturbance including scintillations, scotoma or blindness associated with migraine headache. they can occur at the same time as migraine, headache and are sometimes seen in a patient with a prior history of migraine. They occur because of hypoperfusion of either the eye or the optic nerve. This is a different entity to typical migraine with aura, which involves the cerebral cortex and is associated with binocular visual phenomena. Here I am reporting a case of retinal migraine in a 22 years old female patient from the OPD of Department of Neurology, Patna medical College and Hospital, Patna.